Preferensi Penyedia Jasa Terhadap Penerapan Kebijakan Penggunaan Aspal Plastik Sebagai Bahan Konstruksi Jalan - Didan Saeful Rohman El Karim; Herman Herman; Ida Farida; Adhitya Surya Pratama; Madi Hermadi (Institut Teknologi Garut, 2023)
The amount of waste thrown away by the community in Garut Regency reaches thousands of tons per day, on the other hand, the capacity at the Pasir Bajing landfill is very limited. Various types of waste, including plastic waste, can be utilized and processed so that they have useful value. The Regional Government of Garut Regency has innovated by using waste in the form of plastic as aggregate mixed with asphalt called plastic asphalt as a flexible road construction material. This is an effort to increase the efficiency and effectiveness of the use of road construction in the Garut Regency area. The aim of this research is to determine and analyze the preferences of service providers, both contractors and supervisory consultants, regarding the implementation of the policy of using plastic asphalt as a road construction material in Garut Regency. The research method uses quantitative descriptive methods. The sample consisted of 100 people consisting of contractors and supervisory consultants involved in the implementation of plastic asphalt in Garut Regency. The results of the analysis of product quality, satisfaction with use, and implementation of policies on the use of plastic asphalt are good and need to be maintained.